Comprehensive investigations of (Ti-6Al-4V - AA7075 / engine oil) nanofluid flowing with thermal radiative heat flux: significant upshots - Hussain, Syed M.; Arshad, Misbah; Ahmad, Hijaz; Jamshed, Wasim; Guedri, Kamel; Qureshi, Muhammad Amer; Mohamed Isa, Siti Suzilliana Putri; Almaliki, Abdulrazak H.; Bayram, Mustafa (Elsevier, 2025)
A small number of researchers have investigated the fundamental nature of nanomaterials, specifically regarding the symmetrical elongated surface effectiveness of third-grade nano-liquids (3-GNF). In this article, motor oil is selected as the common base fluid for the 3-GNF version. This decision was inspired by the Tiwari and Das fluid model. Tiwari and Das examined the percentage of nanoparticles in the Buongiorno model, considering thermophoresis and Brownian diffusion variables. Because of this, the thermal performance of 3-GNF is investigated in the study that is now being written. Because of this, the conceptual model utilizes symmetry in its description. To generate nonlinear ordinary differential equations, it is necessary to first use the transformation method to partial differential equations that are generated using the boundary-layer formulation. The final numerical solutions are then obtained by using the homotopy evaluation technique in Mathematica, which is a part of the semi-analytical machine. It is taken into consideration that titanium alloys (Ti-6Al-4V) and aluminum alloys (AA7075) also exist. There is a significant difference in the thermal performance of the Ti-6Al-4V-EO nanofluid and that of the AA7075-EO nanofluid, as determined by the numerical results that were done in the same condition. Moreover, the thermal Biot number increases temperature while variable thermal conductivity decreases it. Further, the spongy medium reduces the thermal source charge and enhances rate variation. Finally, the effect of Reynolds and Brinkman numbers is increasing entropy. The present framework is beneficial in the medicinal and commercial domains, especially in the areas of biomedical cooling technologies, drug delivery, and the treatment of hyperthermia.